Geological repository systems for safe disposal of spent nuclear fuels and radioactive waste - Apted, Michael J.; Ahn, Joonhong (WP Publishing, 2017)
Geological Repository Systems for Safe Disposal of Spent Nuclear Fuels and Radioactive Waste, Second Edition, critically reviews state-of-the-art technologies and scientific methods relating to the implementation of the most effective approaches to the long-term, safe disposition of nuclear waste, also discussing regulatory developments and social engagement approaches as major themes. Chapters in Part One introduce the topic of geological disposal, providing an overview of near-surface, intermediate depth, and deep borehole disposal, spanning low-, medium- and high-level wastes. Part Two addresses the different types of repository systems – crystalline, clay, and salt, also discussing methods of site surveying and construction. The critical safety issue of engineered barrier systems is the focus of Part Three, with coverage ranging from nuclear waste canisters, to buffer and backfill materials. Lastly, Parts Four and Five focus on safety, security, and acceptability, concentrating on repository performance assessment, then radiation protection, environmental monitoring, and social engagement. Comprehensively revised, updated, and expanded with 25% new material on topics of current importance, this is the standard reference for all nuclear waste management and geological repository professionals and researchers.--Provided by publisher.